2021
DOI: 10.1007/s00425-021-03786-y
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the major metabolic pathways associated with aluminum tolerance in popcorn roots using label-free quantitative proteomics

Abstract: Aluminum toxicity is one of the most important abiotic stresses that affect crop production worldwide. The soluble form (Al 3+ ) inhibits root growth by altering water and nutrients uptake, which also reduces plant growth and development. Under a long term Al 3+ exposure, plants can activate several tolerance mechanisms, and to date, there are no reports of large-scale proteomic data of maize in response to this ion. To investigate the posttranscriptional regulation in response to Al toxicity, we performed a l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 77 publications
(88 reference statements)
1
9
0
2
Order By: Relevance
“…CSs are known to respond to abiotic stress 30,31 . For example, a combination of transcriptomic and proteomic data indicated that CS is a key detoxification enzyme for aluminum toxicity in a tolerant maize line 32 . In our study, under 0.45 μM ISA exposure, each of the three OECS4 lines (OECS4‐4, 8, 11) showed weak growth compared to WT (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…CSs are known to respond to abiotic stress 30,31 . For example, a combination of transcriptomic and proteomic data indicated that CS is a key detoxification enzyme for aluminum toxicity in a tolerant maize line 32 . In our study, under 0.45 μM ISA exposure, each of the three OECS4 lines (OECS4‐4, 8, 11) showed weak growth compared to WT (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Studies have shown that Al stress leads to energy deprivation in plant growth and development. As a result, tolerant plants accumulate high levels of glucose to produce adequate ATP through glycolysis [ 12 , 13 , 44 ]. For instance, in Al-tolerant rice, Wang et al [ 14 ] showed that glycolytic pathway proteins are enhanced, which could maintain basic respiration needs and/or generate ATP for Al stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the total TCA cycle metabolites had a weak positive correlation with the total ETC metabolites. The increase in glycolytic flux under Al stress proved that carbon skeletons produced via glycolysis are used primarily for OA production to detoxify Al ions, thereby promoting Al tolerance [13,50,51]. Although some of the total metabolites showed a non-significant (p > 0.05) weak correlation with other metabolites, the CBC, glycolysis and PPP shared common metabolites which showed significant (p < 0.05) associations (Figure 5; Table S2).…”
Section: Associations Between Central Carbon Metabolitesmentioning
confidence: 96%
See 1 more Smart Citation
“…Label-free quantitative (LFQ) proteomics is an effective method for studying the proteome, which is helpful to explore the molecular mechanism of abiotic stresses tolerance. In the past few years, LFQ proteomic analysis have been applied to reveal the response mechanisms of plant roots to abiotic stresses, including flooding, drought, heavy metal, and low N ( Nanjo et al., 2013 ; Xin et al., 2016 ; Jozefowicz et al., 2017 ; Borges et al., 2019 ; Pinto et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%